The Fruitfulness of the Eucharist Offered for the Living and the Dead According to Isaac of Nineveh Based on His Discource XI from the Third Collection - Żelazny, Jan Witold (Vox Patrum, 2026)
In the recently published Mistic treatises of St. Isaac of Nineveh, a passage appeared in Collection III raising the rarely analyzed contemporary issue of the fruitfulness of the Eucharistic Sacrifice offered for the living and the dead. For St. Isaac, this Sacrifice benefits all members of the Church, except for one group, the heretics who reject the truth of Christ’s Presence in the Eucharist. Such a view, clearly valuing orthodoxy, recognizing human weakness as a non-excludable element from the Church community, turns out to be, by comparison with other works from this cultural circle /Letters of Timothy I and Dialogue with a Jew by Sergius Stylites) widespread and emphasizing the role of orthodoxy, the preservation of which gives every member of the Church a share in the saving sacrifice of Christ made present in the Eucharist, both during life and after death.